The Hobby Lobby Case and Arguments around an Equal Rights Amendment - Archer, Madeleine (Maine Policy Review, 2019)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2019 asked students to assess the arguments for and against an Equal Rights Amendment.